Technical Determinant of Road Accident: A Systematic Review - Hawa Harith, Siti; Mahmud, Norashikin (International Journal of Engineering and Technology, 2018)
Road accident statistics has been reported increasing over the years and become one of the significant death contributors worldwide. In response towards this issue, appropriate countermeasures need to be outlined. Proposing a preventive plan requires comprehensive understanding on factors behind the occurrence of road accident. Therefore, this review paper aimed at investigating the factors behind the occurrence of road accident focusing on the technical factors. A review over five academic databases such as Emerald, ScienceDirect, Scopus, Web of Science and Wiley Online Library has been conducted leading towards an overall finding of 2462 related records. After screening and reviewing the records, only 38 studies were included. The result of the review indicated several technical factors in terms of road and vehicle faulty toward the occurrence of road accident.Â Â